2009
DOI: 10.1080/13607860902879441
|View full text |Cite
|
Sign up to set email alerts
|

Dementia caregiving in spousal relationships: A dyadic perspective

Abstract: Objectives: The number of couples facing a dementia diagnosis for one partner of the spousal dyad increases. Spousal caregiving can be a highly stressful experience associated with negative caregiver outcomes such as depression and poorer immune function. However, surprisingly little is known about how the illness and the required care effects patient's well-being and relational changes experienced by afflicted couples. The aim of this study was to provide a literature review on how the dyadic perspective is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
157
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(170 citation statements)
references
References 62 publications
1
157
0
12
Order By: Relevance
“…Guidelines suggest interpreting severity of burden as follows: 61-88 as severe, 41-60 as moderate, 21-40 as weak, and scores under 21 as hardly at all (Braun et al, 2010). To assess depression in caregivers, we used the short form of the Allgemeine Depressionsskale (ADS-K; Hautzinger and Bailer, 1993), the German version of the Center for Epidemiologic Studies Depression Scale (CES-D; Radloff, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…Guidelines suggest interpreting severity of burden as follows: 61-88 as severe, 41-60 as moderate, 21-40 as weak, and scores under 21 as hardly at all (Braun et al, 2010). To assess depression in caregivers, we used the short form of the Allgemeine Depressionsskale (ADS-K; Hautzinger and Bailer, 1993), the German version of the Center for Epidemiologic Studies Depression Scale (CES-D; Radloff, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that FCs' negative thoughts and feelings of burden could cause them to focus on their relatives' weaknesses, creating a vicious cycle in the family, during which the FCs' negative orientation lead to negative responses and actions from the PMD, exacerbating tension. Previous research has shown that good quality of daily relationships and positive reciprocal communication can promote FCs' wellbeing [31,45,46] and support the positive adjustment of PMDs. It has also been found that enhanced relationship quality can maintain better emotional wellbeing of both the PMD and the FC, which can lead to more positive experiences of living with a memory disorder [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Issues relevant to family members' experiences that have been studied include changes in relations as well as caregivers' challenges, well-being, burden and coping mechanisms [8,[26][27][28][29] . Intrapersonal processes are usually of interest, and investigators highlight a need to understand the interpersonal and dyadic processes involved in giving and receiving care [30,31] . The challenge of living with memory disorders can be seen as a collaborative journey on which family members work together in response to their impact [32,33] .…”
mentioning
confidence: 99%
“…A study by Brittain et al (2010) explored how the social model of disability might be used to promote the citizenship of people with dementia, but whether their experiences of citizenship might also be gendered was not considered. Indeed, as research into the lived experience of dementia tends to explain the domestic lives of couples solely in terms of the illness, the possible influence of gender dynamics (past and present) on roles and responsibilities is given little consideration (for example, Braun et al 2009). Hence, there was a need for indepth research into how people with dementia -especially women -exercise agency within couple relationships, notably through their involvement in everyday decisionmaking processes.…”
Section: The Agency Of Women With Dementia and Everyday Decision-makingmentioning
confidence: 99%
“…Although previous studies examined the challenge that dementia poses to maintaining couple relationships (for example, O'Shaughnessy et al 2010), the authors did not consider whether gender inequality might continue to influence the agency that women with dementia exercise within their relationships, particularly in relation to the microaspects of their daily lives, such as domestic decision-making. Indeed, although research into couple relationships in dementia has frequently explored only the views of the carerspouses, this study examined the perspectives of both spouses (for example, O'Shaughnessy et al 2010, see also Braun et al 2009). …”
Section: The Agency Of Women With Dementia and Everyday Decision-makingmentioning
confidence: 99%